A Study of Spatial Connectivity in Banyumas Old Town Using Space Syntax - Setiawan Dudi Prasetio (Universitas Ichsan Sidenreng Rappang, 2025)
Banyumas Old Town is a heritage asset that reflects the history and urban development of Banyumas Regency. To date, urban dynamics often change the existing spatial configuration in the city, which directly impacts vitality and accessibility. Understanding spatial connectivity is crucial for the preservation and sustainable development of historic areas. This study aims to quantitatively analyze the elements of city image in the form of paths and nodes in the level of spatial connectivity in the Banyumas Old Town area. The main method used is space syntax. This approach studies the regional road network using axial line and visual graph analysis (VGA) for analysis. The key parameters for quantitative calculations include integration, connectivity, and choice. The analysis revealed that not all spaces in Banyumas Old Town have a good level of connectivity. Main corridors were found with high global integration values, which function as the backbone of circulation and commercial activities. Conversely, several zones with important historical value actually show low local integration values, indicating spatial segregation. These findings objectively map the spatial hierarchy and functional potential of the area. The implication is that the revitalization strategy or design direction in Banyumas Old Town can be directed in accordance with the city's image to increase economic and social vitality without including efforts to preserve its historical value.